2021
DOI: 10.1029/2021gl092645
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Ocean Carbon Sink in the South and Central North Sea (2014–2018) Revealed From FerryBox Observations

Abstract: Atmospheric carbon dioxide (CO 2 ) concentration increased by 2.30 ± 0.01 ppm yr −1 during the 2009-2018 period (Friedlingstein et al., 2019). This rate would be higher had the ocean not taken up approximately a quarter of the anthropogenic carbon emitted since the industrial revolution (Le Quéré et al., 2018). This ocean carbon uptake leads to a global increase in the partial pressure of carbon dioxide (pCO 2 ) in the surface ocean (Fay & McKinley, 2013). The sign of the difference between the seawater and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 82 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…This approach has already been implemented in European countries, especially for installation on ferries, with a cost of around 50,000 Euros (Kuznetsov et al, 2019;Peterson, 2019). Furthermore, this instrument has been able to produce data that can map several phenomena, such as upwelling (Irion, 1998;Langis, 2015), water quality monitoring (Gunia et al, 2022) and carbon sink analysis (Macovei et al, 2021). In Indonesia, the concept of a low-cost instrument to monitor the ocean have been successful with RHEA and ARHEA instrument (Purba et al, 2019;Zenyda et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has already been implemented in European countries, especially for installation on ferries, with a cost of around 50,000 Euros (Kuznetsov et al, 2019;Peterson, 2019). Furthermore, this instrument has been able to produce data that can map several phenomena, such as upwelling (Irion, 1998;Langis, 2015), water quality monitoring (Gunia et al, 2022) and carbon sink analysis (Macovei et al, 2021). In Indonesia, the concept of a low-cost instrument to monitor the ocean have been successful with RHEA and ARHEA instrument (Purba et al, 2019;Zenyda et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has already been implemented in European countries, especially for installation on ferries, with a cost of around EUR 50,000 [ 20 , 21 ]. Furthermore, this instrument has been able to produce data that can map several phenomena, such as upwelling [ 22 , 23 ], water-quality monitoring [ 19 , 24 ], and carbon sink analysis [ 25 ]. Previous findings, for instance, in Indonesia, with the concept of low-cost ocean monitoring instruments have been successfully applied with the RHEA and ARHEA instruments [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Voynova et al (2018) combined data from three FBs to characterize regional water masses in the German Bight and the North Sea and showed the dependence of dissolved inorganic carbon on salinity. Macovei et al (2021) used the FB to study the average annual variability of pCO 2 . They showed that the trend of partial pressure of carbon dioxide in the surface layer of seawater in 2014-2018 in the southern and central North Sea increased larger than in the atmosphere, and this caused a rise in the average flow of CO 2 from the sea to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%